MICROBIOLOGICAL SURVEILLANCE OF OPERATION THEATRES OF A TERTIARY CARE HOSPITAL IN BIHAR. - KUMAR, Binay Kumar Mahto; Shreya ,; Sanjay Kumar ,; Rajesh Kumar , (Student's Journal of Health Research Africa, 2024)
Background Microbial contamination of air and environment in operation theatres (OTs) has continued to increase the prevalence of surgical site and hospital-associated infections. Control of these infections in operation theatres is of utmost importance as it can increase patient’s morbidity and mortality. Aims and Objectives Aim of the present study was to identify bacterial colonization of surfaces and to determine the microbial contamination of air by estimating the bacterial colony forming unit (CFU) rate in the OT’s of a tertiary care hospital. Material and Method This was the tertiary care hospital based retrospective observational study done for a period of 18 months. Data was collected from routine microbiological surveillance of OT’s done between February 2023 to July 2024. Two sampling procedures were considered in this study. For air quality surveillance, settle plate method whereas for surface sampling, soaked swabs from different sites in peptone water were included. Collected samples were transported to Microbiology Laboratory of the institution in sterile condition and careful observation was done of bacterial species, which were isolated and further identified by conventional methods. Results A total of 463 samples were collected from different surfaces of various OT’s. Out of these 130 samples showed bacterial growth. The predominant species isolated was Aerobic Spore-Forming Bacilli with 87/130 isolates followed by coagulase-negative Staphylococcus 31/130 , Klebsiella species 8/130 , E.coli 2/130 , Staphylococcus aureus 1/130 & Pseudomonas aeruginosa 1/130. OT’s air samples showed highest colony forming unit (cfu) rate in Labor room (133cfu/m3) and least cfu rate in Radiotherapy (38cfu/m3). Conclusions OTs of our hospital showed highest bacterial contamination in Labor room where the patient load was high and among all the surfaces, OT tables and floor were mostly contaminated with microorganisms.